Distinct brain representations of processed and unprocessed foods. (18th July 2019) - Coricelli, Carol; Toepel, Ulrike; Notter, Marie‐Laure; Murray, Micah M.; Rumiati, Raffaella I.
Abstract: Among all of the stimuli surrounding us, food is arguably the most rewarding for the essential role it plays in our survival. In previous visual recognition research, it has already been demonstrated that the brain not only differentiates edible stimuli from non‐edible stimuli but also is endowed with the ability to detect foods' idiosyncratic properties such as energy content. Given the contribution of the cooked diet to human evolution, in the present study we investigated whether the brain is sensitive to the level of processing food underwent, based solely on its visual appearance. We thus recorded visual evoked potentials (VEPs) from normal‐weight healthy volunteers who viewed color images of unprocessed and processed foods equated in caloric content. Results showed that VEPs and underlying neural sources differed as early as 130 ms post‐image onset when participants viewed unprocessed versus processed foods, suggesting a within‐category early discrimination of food stimuli. Responses to unprocessed foods engaged the inferior frontal and temporal regions and the premotor cortices. In contrast, viewing processed foods led to the recruitment of occipito‐temporal cortices bilaterally, consistently with other motivationally relevant stimuli. This is the first evidence of diverging brain responses to food as a function of the transformation undergone during its preparation that provides insights on the spatiotemporal dynamics of food recognition. Abstract : Extracting information about food edibility and identity by eye is a critical ability for our survival. Using electrical neuroimaging, we investigated the spatio‐temporal dynamics of visual food categorization as a function of the food's level of transformation. Our visual evoked potentials and neural sources results revealed, for the first time, that unprocessed‐processed food discrimination occurrs as early as 150 ms post‐image onset.